An investigation into sector designation, prescribed in the Preferential Procurement Policy Framework Act (PPPFA), as a policy instrument for broadening the transformer industry's industrial base - Chibanguza, Tafadzwa C (My University, 2016)
The paper identifies that due to the historic evolution of the South African economy, particularly the emphasis placed on energy provision as a catalyst for successful mineral extraction; the seeds were sown for South Africa to be an industrial hub in transformer manufacturing. However, this opportunity has not been realised. Domestic transformer manufacturers have continued to lose market share both domestically and globally. The research identifies a lack of demand, locally, for domestically manufactured transformers as an inherent cause of the challenges faced by the local transformer industry. This lack of demand is also recognized as the reason constraining the potential growth of the industry. The paper identifies a virtuous cycle between capacity utilization and expansion, wherein; higher capacity utilization favourably influences price competitiveness, which increases market share and induces investment into additional capacity. As greater market share is 2 | P a g e attained due to price competitiveness, even higher capacity utilization is achieved; therefore further inducing investment on the expanded capacity and the cycle continues with further expansion. The paper investigates sectoral designation as an industrial policy instrument to achieve this model, that is; increase demand, capacity utilization and ultimately broaden the industrial base of transformer manufacturing. The paper advocates that, while growing in the export market is the ideal end point, the industry would grow its current production capacity threefold if it were provided the opportunity to fully satisfy domestic demand1. As a result, this should be the first market to conquer. It is also identified in the research that sectoral designation as a policy instrument is not without shortfalls, particularly given the unique characteristics inherent in the transformer industry. The paper concludes with policy recommendations to overcome the identified shortfalls and proposes a model for consideration. This dissertation is submitted for the completion of a Master of Commerce in Development Theory and Policy degree. I would like to express utmost gratitude to Dr Paul Jourdan for his supervision, guidance and valuable contribution in the preparation of this research report.
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2016.
Keywords: Electric transformer industry--South Africa; Industrial policy--South Africa; Electric power distribution--South Africa